Hubungan Faktor Manusia dan Lingkungan Rumah Terhadap Kejadian Tuberkulosis di Wilayah Kerja Puskesmas Rejosari Kota Pekanbaru - Suci Fanesa Febrilia; Buchari Lapau; Kamali Zaman; Mitra Mitra; Musfardi Rustam (Jurnal Kesehatan Komunitas, 2022)
Background: Tuberculosis (TB) is an infectious disease caused by tuberculosis mycobacterium. Rejosari health center found the highest TB frequency among all health centers in Pekanbaru municipality. The research objective was to find the relationship between Human Factors and the Home Environment on the Occurrence of Tuberculosis in the Working Area of ​​Rejosari Health Center, Pekanbaru municipality. Method: The design type is a case-control study. The case and control population were taken from January 2018 to June 2020. The case sample (223) was taken from its population (255) and the control sample (223) was taken from its population (566) by systematic random sampling. Data collection through structured interviews using a questionnaire containing the closed-ended question, and using univariate, bivariate, and multiple logistic regression analysis. Results: there are 8 independent variables related starting from the most dominant, namely age OR=2.8 (95% CI: 1.58-5.00), BCG immunization OR=2.2 (95% CI:1.35-3.63), space humidity OR = 2.2 (95% CI: 1,42-3,31), ventilation area OR = 1.7 (95% CI: 1,12-2,64), gender OR = 1.7 (95% CI: 1,12-2,64), asset ownership OR = 2.9 (95% CI: 1.45-6.03), history of household contacts OR = 2.7 (95% CI: 1.73-4.22) and occupancy density OR = 2 (95% CI: 1.31-3.10). The OR value on the interaction variable (sex with age) indicates that productive-age men are 4.32 times riskier in suffering TB than productive-age women. Recommendation: TB prevention should be conducted through intervention by increasing BCG vaccination coverage, fulfilling space humidity, ventilation area, and occupancy density, and isolating household contact, especially for productive age, men, and low logistic ownership families. Suggestions are formulated based on recommendations.